If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3x = -1 Solving 7 + 3x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3x = -1 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = -1 + -7 3x = -1 + -7 Combine like terms: -1 + -7 = -8 3x = -8 Divide each side by '3'. x = -2.666666667 Simplifying x = -2.666666667
| -3t+2=-3t-10 | | x/2=0 | | 2x-7+5x+1=23 | | 9(v+1)-3v=2(3v+2)-10 | | y-9/y^2-y+9/6y | | 5x-3+2x=13-x | | -2/3x=-5 | | -3a-a=-4 | | 6(2+4)-1/2*3+1= | | -(2x-7y+7)= | | b+13/2=-5b/3 | | -22=5x+6x | | 6y-6(3y-11)= | | 2v+7v=-9 | | 13x-7=3(4x+5)-8 | | x-21/2 | | -11+51=-5(x+2) | | m+8+6=22 | | x=-3y-8y+3x-9 | | 2x+2=35+5x | | y-3y-10=0 | | 4a+3+2a=15 | | 5(d-5)+12= | | -13=2m+1 | | 7-2x-5-10x=5 | | p=2(d+w) | | -3(n+7)= | | 2x^2-5x+6=1 | | -69-4z=3+5x | | f^5-20/4+12+2^3 | | 5=5x-2 | | x-0.15+10.00=180 |